Enabling internal electronic circuitry within additively manufactured metal structures – the effect and importance of inter-laminar topography. Issue 1 (2nd January 2018) - Li, Ji; Monaghan, Tom; Kay, Robert; Friel, Ross James; Harris, Russell
Abstract : Purpose: This paper aims to explore the potential of ultrasonic additive manufacturing (UAM) to incorporate the direct printing of electrical materials and arrangements (conductors and insulators) at the interlaminar interface of parts during manufacture to allow the integration of functional and optimal electrical circuitries inside dense metallic objects without detrimental effect on the overall mechanical integrity. This holds promise to release transformative device functionality and applications of smart metallic devices and products. Design/methodology/approach: To ensure the proper electrical insulation between the printed conductors and metal matrices, an insulation layer with sufficient thickness is required to accommodate the rough interlaminar surface which is inherent to the UAM process. This in turn increases the total thickness of printed circuitries and thereby adversely affects the integrity of the UAM part. A specific solution is proposed to optimise the rough interlaminar surface through deforming the UAM substrates via sonotrode rolling or UAM processing. Findings: The surface roughness (Sa) could be reduced from 4.5 to 4.1 µ m by sonotrode rolling and from 4.5 to 0.8 µ m by ultrasonic deformation. Peel testing demonstrated that sonotrode-rolled substrates could maintain their mechanical strength, while the performance of UAM-deformed substrates degraded under same welding conditions ( approximately 12 per cent reduction compared with undeformed substrates). This was attributed to the work hardening of deformation process which was identified via dual-beam focussed ion beam–scanning electron microscope investigation. Originality/value: The sonotrode rolling was identified as a viable methodology in allowing printed electrical circuitries in UAM. It enabled a decrease in the thickness of printed electrical circuitries by ca. 25 per cent.